Histopathological and behaviour effects of formaldehyde treatment in juvenile mullet, Mugil liza (Valenciennes) - Pahor-Filho, Eduardo [UNESP]; Miranda Filho, Kleber Campos; Klosterhoff, Marta; Romano, Luis Alberto; Pereira Júnior, Joaber (Hindawi, 2015)
Considerable losses may be related to diseases caused by parasites in aquaculture. Formaldehyde (37% gas dissolved in water) is an effective chemotherapeutic, widely used to control ectoparasites in fish. However, for many species of fish used in aquaculture, the control of external parasites and the deleterious effects of formaldehyde in short-term baths are still uncertain. In order to clarify some gaps, 1 h-prophylactic baths (67.5, 135, 270, 405 and 540 mg L-1 formaldehyde in triplicate) were performed in juvenile mullet, Mugil liza (Valenciennes). Results showed that prophylactic baths of 135 mg L-1 formaldehyde by 1 h did not cause death in tested mullets. At this concentration, histopathologies were mild and fish survival was high. However, fish exposed to increasing concentrations of formaldehyde presented severe histopathologies in the gills besides behavioural and morphological alterations. The histopathological and behavioural implications of formaldehyde use in aquaculture are discussed. © 2015 John Wiley
Keywords: Chronic toxicity; Ectoparasites; Gill histopathology; Treatment